The power of legitimate naming. Part I - Chief constables as social commentators in post-war England - Loader, Ian (The British journal of criminology, 2001)
This paper - which appears in two separate parts - traces the advent since 1945 of chief constables as significant commentators on both law and order' in particular and the state of the nation' more generally. Drawing upon autobiographies (and other writings), force annual reports, and interviews with serving and retired chiefs, we set out to understand how police elites have come to acquire the power to legitimately name', diagnose and classify social problems. We set out - in Part I - to chart the transformation of chief officers from powerful (but essentially) local figures in the 1950s and 1960s, through the rise of maverick, culturally prominent police heroes' in the 1970s, to the establishment of a more corporate (and generally liberal) police voice since the late 1980s; and document the themes, imagery and preoccupations that have characterized the senior police outlook during what we distinguish as three distinct periods of mobilization - 1945-72, 1973-86 and 1987-present. In Part II (Loader and Mulcahy 2001), we proceed to develop a sociological interpretation of the emergence and subsequent transformation of the elite police voice